A test of strategic optimality theory: evidence from the social networking industry. Issue 2 (3rd April 2019) - Ching, Kenny
ABSTRACT: In this empirical study I examine the theory of strategic optimality in the context of developing an effective entrepreneurial strategy. The study's novel approach leverages a unique development in entrepreneurship: from 2006 to 2011, there arose in China several Facebook 'clones' – ventures based on the same entrepreneurial opportunity but without any competition from Facebook thanks to the Chinese state's Internet firewall. I present evidence drawn from this setting that is based on a new hand-collected data set that records activity by all entrants into the Chinese social networking industry during that period. The analysis yields robust results indicating that the benefits of differentiation strategy are nuanced; although differentiated firms were more likely to receive venture capital investment, they also experienced declines in interim performance. The core results hold after incorporating excluded instruments developed from the parallel developments of the US social network industry, which serve as exogenous sources of variation. My findings extend the literature on entrepreneurship and strategy by lending a temporal view towards strategic optimality theory. In so doing, I provide evidence that the organisational life-cycle provides a useful and central guide with regard to the management of the conformity and differentiation of a firm, thereby providing direct and practical advice to the strategic entrepreneur.